The changes in CD4+CD25high T cells and TGFβ1 levels in different stages of adult-onset Type 1 diabetes: Stages in T1D: differences in CD25high T cells and TGFβ1 - Miličić, Tanja; Jotic, Aleksandra; Markovic, Ivanka; Popadic, Dusan; Lalic, Katarina; Uskokovic, Veljko; Lukic, Ljiljana; Macesic, Marija; Stanarcic, Jelena; Stoiljkovic, Milica; Milovancevic, Mina; Rafailovic, Djurdja; et al. (Journal of Medical Biochemistry, 2024)
Background. Previous studies suggested important role of impairments in T cells subsets in different stages during type 1 diabetes (T1D) development, while data regarding CD25high T cells and transforming growth factor β1-TGFβ1, both T regulatory associated, still remains controversial. We analysed the level of (a) CD25high T cells (b) TGFβ1 in 17 first-degree relatives of patients with T1D in stage 1 (FDRs1) (GADA+, IA-2+); 34 FDRs in stage 0 (FDRs0) (GADA-, IA-2-); 24 recent-onset T1D in insulin requiring state (IRS); 10 patients in clinical remission (CR); 18 healthy, unrelated controls (CTR). Methods. T cell subsets were characterized by two-color immunofluorescence staining and flow cytometry, TGFβ1 was determined by ELISA, GADA, and IA-2 by RIA. Results. The level of CD25high T cells in FDRs1 was lower than controls, FDRs0, IRS, and CR (p<0.001). Additionally, the cut-off point for CD25high = 1.19%, with a probability of 0.667, for having a higher risk for T1D. TGFβ1 level in FDRs1, FDRs0, IRS, and CR, was lower than controls (p<0.001). IRS has a higher TGFβ1 level than CR (p<0.001). Conclusions. Stage 1, a higher risk for T1D, is characterized by decreases in CD25high T cells and TGFβ1, partially reflecting impaired T regulatory response, implying that changes of this T cells subset might be a risk marker for T1D. FDRs irrespective of risk for T1D and T1D patients irrespective of state, had depletion of TGFβ1, suggesting the association of TGFβ1 with familiar risk and manifestation of T1D. Furthermore, clinical course of overt T1D might be modulated on TGFβ1 level.